Porous membranes and purification methods
By developing porous membranes with negatively charged polymers and uneven structures, the problem of porous membrane blockage during antibody drug purification is solved, and efficient purification and IgG recovery are achieved.
Patent Information
- Application Number
- CN202380060578.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-17
- Publication Date
- 2025-03-28
AI Technical Summary
During the purification of antibody drugs, existing porous membranes are prone to clogging due to the presence of various substances in the cells, resulting in reduced purification efficiency and failure of porous membranes.
A porous membrane containing a negatively charged polymer has an uneven structure, a capture layer with a high transmittance of 10 nm colloidal gold and a 20 nm colloidal gold, combining hydrophobic and hydrophilic polymers to inhibit blockage and improve purification efficiency.
The agglomerates that simultaneously adsorb and remove positively charged substances and IgG are achieved, which improves the recovery rate of IgG in monomer state, and effectively suppresses the blockage of the porous membrane and extends its service life.
Smart Images

Figure CN119730946A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous membrane and a purification method. Background Art
[0002] For example, when producing antibody drugs, cation exchange membranes are used to adsorb and remove positively charged substances contained in host cell-derived proteins (HCP) in the process of purifying antibodies (IgG, etc.) by removing impurities from cultured cells.
[0003] The cation exchange membrane needs to be negatively charged in order to adsorb positively charged substances such as proteins. Examples of such cation exchange membranes include "Mustang S" sold by Pall Corporation and "Sartobind S" sold by Sartorius Stedim Biotech S.A.
[0004] Here, as such a negatively charged porous membrane (cation exchange membrane), the present inventors have developed a porous membrane containing a polymer having a negative (anionic) charge and the like, which can be used for separation of blood and the like.
[0005] Patent Document 1 (Japanese Patent No. 3651682) discloses an ion exchange membrane including a sulfonated polyarylene ether copolymer.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 3651682 Summary of the invention
[0009] Problems to be solved by the invention
[0010] When such a porous membrane containing a negatively charged polymer (cation exchange membrane) is used to purify antibodies, Figure 4 As shown, it is desirable to provide a porous membrane which, in addition to removing positively charged substances in HCP by adsorption, can also fractionate and remove IgG aggregates and allow non-aggregated monomeric IgG to pass therethrough, thereby enabling recovery of monomeric IgG.
[0011] However, the porous membrane having such a function is prone to clogging over time due to various substances contained in the cells. Therefore, it is desirable to provide a porous membrane that can suppress the occurrence of clogging caused by various substances contained in the treatment object liquid and can be used continuously and stably.
[0012] Therefore, the object of the present invention is to provide a porous membrane which, when using a porous membrane containing a negatively charged polymer to purify an antibody drug, can simultaneously perform adsorption and removal of positively charged substances and size fractionation removal of IgG aggregates, can recover IgG in a monomeric state at a high recovery rate, and can inhibit the occurrence of clogging of the porous membrane.
[0013] Means for solving problems
[0014] (1) A porous membrane comprising a polymer having a negative charge,
[0015] The porous membrane has a non-uniform structure in the thickness direction, wherein the first surface is sparse and the second surface is dense.
[0016] In the porous membrane, the transmittance of colloidal gold having an average particle size of 10 nm from the first surface side to the second surface side is 5% or more,
[0017] The porous membrane does not have the ability to transmit colloidal gold having an average particle size of 30 nm from the first surface side to the second surface side.
[0018] When colloidal gold having an average particle size of 20 nm is allowed to pass from the first surface side to the second surface side of the porous membrane, the ratio of the thickness of the capture layer to the thickness of the porous membrane is greater than 10%, and the capture layer is a layer that captures the colloidal gold having an average particle size of 20 nm.
[0019] (2) The porous membrane according to (1), further comprising a hydrophobic polymer and a hydrophilic polymer.
[0020] (3) The porous membrane according to (2), wherein the hydrophobic polymer is at least one of polysulfone and polyethersulfone.
[0021] (4) The porous film according to (2) or (3), wherein the hydrophilic polymer is at least one of polyvinyl pyrrolidone and a copolymer of vinyl pyrrolidone and vinyl acetate.
[0022] (5) The porous membrane according to any one of (1) to (4), wherein the negatively charged polymer comprises repeating units of a hydrophobic segment represented by the following formula (1) and repeating units of a hydrophilic segment represented by the following formula (2) as copolymer components.
[0023] [Chemical formula 1]
[0024]
[0025] [Chemical formula 2]
[0026]
[0027] The composition ratio (molar ratio) of the above formula (1) is 0.50 to 0.65, the composition ratio (molar ratio) of the above formula (2) is 0.35 to 0.50, the total of the composition ratio (molar ratio) of the above formula (1) and the composition ratio (molar ratio) of the above formula (2) is 1.00, R1 and R2 represent "-SO3M", and M represents a metal element.
[0028] (6) The porous membrane according to any one of (1) to (5), which has a hollow fiber membrane shape in which the inner surface side is sparse and the outer surface side is dense.
[0029] (7) The porous membrane according to any one of (1) to (6), which is used for purification by cation exchange.
[0030] (8) A purification method using the porous membrane according to any one of (1) to (7).
[0031] Effects of the Invention
[0032] According to the present invention, a porous membrane can be provided, which, when using a porous membrane containing a negatively charged polymer to purify an antibody drug, can simultaneously perform adsorption and removal of positively charged substances and size fractionation and removal of IgG aggregates, can recover IgG in a monomeric state at a high recovery rate, and can inhibit the occurrence of clogging of the porous membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram for explaining an example of a method for producing a porous film.
[0034] Figure 2 is a schematic diagram for explaining depth filtration.
[0035] Figure 3 This is a diagram for explaining surface filtration (screen filtration).
[0036] Figure 4 This is a schematic diagram for explaining the function of the porous membrane according to the embodiment.
[0037] Figure 5 This is a graph showing the amount of lysozyme adsorbed per unit volume of the porous membranes of Comparative Example 1, Example 1, and the like.
[0038] Figure 6 This is a graph showing the relationship between the filtration time and the cumulative filtration capacity per unit area for the porous membranes of Comparative Example 1 and Example 1.
[0039] Figure 7 It is a schematic diagram for explaining dead-end filtration in each measurement method.
[0040] Figure 8 This is a SEM image of a cross section of the porous membrane of Example 1. Figure 8 (a) is the cross section of the porous membrane, Figure 8 (b) is an enlarged image of the first surface (inner surface). Figure 8 (c) is an enlarged image of the second surface (outer surface).
[0041] Fig. 9 This is a SEM image of a cross section of the porous membrane of Comparative Example 1. Fig. 9 (a) is the cross section of the porous membrane, Fig. 9 (b) is an enlarged image of the first surface (inner surface). Fig. 9 (c) is an enlarged image of the second surface (outer surface).
[0042] Fig.10 This is an image obtained using a microscope of a cross section of a hollow fiber membrane after filtering a 20 nm colloidal gold dispersion. Fig.10 (a) is the imaging of Comparative Example 1, Fig.10 (b) is the imaging of Example 1. Fig.10 (c) is a cross section of the hollow fiber membrane after filtering in the reverse direction (from the outside to the inside) of the hollow fiber membrane of Example 1.
[0043] Fig.11 This is a schematic diagram of a ring-shaped micromodule (Japanese: ミニモジュール).
[0044] Fig.12 It is used Fig.11 Schematic diagram of dead-end filtration of annular micromodules.
[0045] Fig.13 This is a graph showing the relationship between the ratio of the cumulative filtration amount and the lysozyme concentration in the lysozyme adsorption experiment. DETAILED DESCRIPTION
[0046] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited thereto.
[0047] <Hollow fiber membrane>
[0048] [Material of hollow fiber membrane]
[0049] The hollow fiber membrane of the present embodiment includes a hydrophobic polymer, a negatively charged polymer, and a hydrophilic polymer.
[0050] (Hydrophobic polymer)
[0051] Examples of the hydrophobic polymer include polysulfone-based polymers such as polysulfone and polyethersulfone; cellulose-based polymers such as cellulose acetate and cellulose derivatives; and polyolefin-based polymers such as polyethylene. Polyethersulfone is a compound containing a structural unit represented by the following formula (3).
[0052] [Chemical formula 3]
[0053]
[0054] Specific examples of polyethersulfone include Ultrason (registered trademark) E2020P and E6020P manufactured by BASF, and SUMIKAEXCEL (registered trademark) 3600P, 4100P, 4800P, 5200P, and 7600P manufactured by Sumitomo Chemical Co., Ltd., preferably E6020P, 4800P, or 5200P. These may be used alone or in combination.
[0055] (Polymer with negative charge)
[0056] Examples of the negatively charged polymer include: ionomers containing at least one of polystyrene sulfonic acid, poly(trifluorostyrene) sulfonic acid, polyvinylphosphonic acid, polyvinyl carboxylic acid, and polyvinyl sulfonic acid components; polymers containing at least one of aromatic polymers, polysulfone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyphenylene sulfide sulfone, polyparaphenylene, polyarylene polymers, polyphenylquinoxaline, polyaryl ketone, polyetherketone, polybenzoxazole, polybenzothiazole, polyimide, etc., into which at least one of sulfonic acid groups, phosphonic acid groups, carboxyl groups, and derivatives thereof are introduced, etc. Among these, polyarylether compounds such as polysulfone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyphenylene sulfide sulfone, and polyetherketone polymers containing sulfonic acid groups are preferably used.
[0057] The sulfonated polyarylene ether copolymer is a compound comprising repeating units of a hydrophobic segment represented by the following formula (1) and repeating units of a hydrophilic segment represented by the following formula (2).
[0058] [Chemical formula 4]
[0059]
[0060] [Chemical formula 5]
[0061]
[0062] The composition ratio (molar ratio) of the above formula (1) is 0.50 to 0.65, the composition ratio (molar ratio) of the above formula (2) is 0.35 to 0.50, the total of the composition ratio (molar ratio) of the above formula (1) and the composition ratio (molar ratio) of the above formula (2) is 1.00, R1 and R2 each independently represent "-SO3M" or "-SO3H", and M represents a metal element.
[0063] The sulfonated polyarylene ether copolymer may be any of a random copolymer, a block copolymer, an alternating copolymer, and the like.
[0064] M (metal element) is not particularly limited, and examples thereof include sodium, potassium, and lithium.
[0065] In the sulfonated polyarylene ether copolymer, the constituent ratio (molar ratio) of the formula (1) is more preferably 0.50 to 0.60, and the constituent ratio (molar ratio) of the formula (2) is more preferably 0.40 to 0.50, and R1 and R2 in the formula (2) are more preferably "-SO3Na" or "-SO3K".
[0066] It should be noted that the sulfonated polyarylether copolymer is a material that undergoes little change over time during long-term use of the membrane.
[0067] The sulfonated polyarylether copolymer can be obtained by a conventionally known method, for example, by reacting 2,6-dichlorobenzonitrile, 3,3'-disulfo-4,4'-dichlorodiphenylsulfone metal salt, and 4,4'-biphenol in the presence of a basic compound and polymerizing them by an aromatic nucleophilic substitution reaction, a copolymer containing a hydrophobic segment represented by the above formula (1) and a hydrophilic segment represented by the above formula (2) can be obtained.
[0068] The polymerization can be carried out at a temperature range of 0 to 350° C., preferably 50 to 250° C. At a temperature below 0° C., the reaction tends not to proceed sufficiently, and at a temperature above 350° C., the polymer tends to begin to decompose.
[0069] The reaction can also be carried out without a solvent, but is preferably carried out in a solvent. Examples of solvents that can be used include N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, diphenyl sulfone, sulfolane, etc., but are not limited to these, as long as the solvent can be used as a stable solvent in an aromatic nucleophilic substitution reaction.
[0070] Examples of the alkaline compound include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, and the like. Any alkaline compound may be used without limitation as long as it can convert the aromatic diol into an active phenoloxy compound structure.
[0071] In the aromatic nucleophilic substitution reaction, water is sometimes generated as a by-product. In this case, toluene or the like can be coexisted in the reaction system independently of the polymerization solvent to remove water outside the system as an azeotrope. As a method for removing water outside the system, a water-absorbing material such as a molecular sieve can also be used.
[0072] When the aromatic nucleophilic substitution reaction is carried out in a solvent, the monomer is preferably added so that the concentration of the obtained polymer becomes 5 to 50% by mass. When the concentration is less than 5% by mass, there is a tendency that the degree of polymerization is difficult to increase. On the other hand, when the concentration is more than 50% by mass, there is a tendency that the viscosity of the reaction system becomes too high and the post-treatment of the reactant becomes difficult.
[0073] After the polymerization reaction is completed, the solvent is removed from the reaction solution by evaporation, and the residue is washed as needed to obtain the desired polymer (sulfonated polyarylether copolymer). Alternatively, the polymer may be precipitated as a solid by adding the reaction solution to a solvent in which the polymer has low solubility, and the precipitate may be filtered to obtain the polymer.
[0074] (Hydrophilic polymer)
[0075] Examples of the hydrophilic polymer include polyvinyl alcohol, polyethylene glycol, vinyl pyrrolidone polymers (polyvinyl pyrrolidone, copolymers of vinyl pyrrolidone and vinyl acetate, etc.), polyacrylic acid, cellulose, methyl cellulose, chitosan, etc. The vinyl pyrrolidone polymer refers to a polymer containing at least a monomer of N-vinyl pyrrolidone.
[0076] The vinyl pyrrolidone polymer preferably includes a structural unit represented by the following formula (4).
[0077] [Chemical formula 6]
[0078]
[0079] Examples of the vinyl pyrrolidone polymer include Kollidon (registered trademark) 30 and 90, and Luvitec (registered trademark) K30, K80, K85, K90, and VA64 commercially available from BASF.
[0080] The content ratio (mass ratio) of the hydrophobic polymer / negatively charged polymer / hydrophilic polymer in the entire hollow fiber membrane is preferably 60 to 90 / 7 to 22 / 3 to 18.
[0081] [Structure of porous membrane, etc.]
[0082] The porous membrane of this embodiment has a non-uniform structure in the thickness direction (asymmetric structure). It should be noted that the porous membrane having an asymmetric structure includes, for example, a porous membrane having different density, porosity, cross-sectional opening ratio, average pore size, etc. in the thickness direction.
[0083] The porous membrane with an asymmetric structure of the present embodiment may be in the shape of a flat membrane or in the shape of a hollow fiber membrane, and preferably has a structure in which the first surface side of its cross section (cross section: cross section in the thickness direction) is sparse and the second surface side is dense. In addition, in the hollow fiber membrane, it may be a structure in which the inner surface side is sparse and the outer surface side is dense (having a dense layer on the outer surface side), or a structure in which the inner surface side is dense (having a dense layer on the inner surface side) and the outer surface side is sparse, and preferably has a structure in which the inner surface side is sparse and the outer surface side is dense (having a dense layer on the outer surface side). In the present embodiment, it is preferred that the treated liquid is passed to the side having a sparse structure (the first surface side), and filtered toward the side having a dense structure (the second surface side).
[0084] In the porous membrane of the present embodiment, the transmittance of colloidal gold having an average particle size of 10 nm from the first surface side (inner surface side) to the second surface side (outer surface side) of the porous membrane is 5% or more, preferably 80% or more, more preferably 90% or more, and further preferably 95% or more.
[0085] In addition, when filtering colloidal gold with an average particle size of 30nm from the 1st surface side (inner surface side) of the porous membrane to the 2nd surface side (outer surface side), it is preferably not permeable. Not having permeability means that the transmittance is below 10%, preferably below 5%, and more preferably below 1%.
[0086] In addition, when colloidal gold having an average particle size of 20 nm is allowed to pass from the first surface side (inner surface side) of the porous membrane to the second surface side (outer surface side), the ratio of the thickness of the capture layer to the thickness of the porous membrane is 10% or more, preferably 20% or more, and more preferably 30% or more, and the capture layer is a layer for capturing colloidal gold having an average particle size of 20 nm.
[0087] It should be noted that the average particle size of colloidal gold refers to the average particle size described in the instruction manual of the product.
[0088] Reference Figure 2 In the cation exchange using the porous membrane 3, antibodies (IgG) and the like in the cell culture fluid are transferred from the extrusion side ( Figure 2 The upper side of the porous membrane: the first surface side of the porous membrane (the inner surface side of the hollow fiber membrane)) passes through the porous membrane 3 and is separated to the second surface side of the porous membrane (the outer surface side of the hollow fiber membrane) ( Figure 2Of the components contained in the cell culture medium, relatively small components 5 (such as IgG) easily pass through the pores of the porous membrane, but, for example, substances with a relatively small size, such as IgG aggregates, are blocked on the first surface (inner surface of the hollow fiber membrane) of the porous membrane (see Figure 4 ) The relatively large component 4 among the small components may sometimes block the pores of the porous membrane. Figure 2 As shown, in filtration (depth filtration) using the porous membrane 3 having an asymmetric structure, the large components 4 are dispersed and captured in the thickness direction of the porous membrane 3 (blocked sequentially in the membrane thickness direction). Therefore, clogging is less likely to occur.
[0089] On the other hand, Figure 3 As shown, when filtering (surface filtration: mesh filtration) is performed using a porous membrane 3 having a uniform structure in the thickness direction, the large-sized components 4 tend to accumulate on the squeeze side of the porous membrane 3 ( Figure 3 The upper side: the first surface side of the porous membrane (the inner surface side of the hollow fiber membrane)) is near the outermost surface, so clogging is likely to occur.
[0090] In the case of a hollow fiber membrane, the inner diameter is preferably 150 μm or more and 400 μm or less, and more preferably 200 μm or more and 350 μm or less.
[0091] The thickness of the porous membrane is preferably 30 to 200 μm, more preferably 40 to 100 μm. The membrane thickness can be calculated from “(outer diameter−inner diameter) / 2”.
[0092] In the case of a hollow fiber membrane, the hollow ratio is preferably 15 to 60%, and more preferably 20 to 50%. It should be noted that the hollow ratio is the ratio of the area of the hollow portion in the cross section of the hollow fiber membrane, and is expressed by "hollow portion cross-sectional area / (membrane portion cross-sectional area + hollow portion cross-sectional area) × 100 (%)". By setting the hollow ratio to the above range, both filtration performance and strength relative to filtration pressure can be taken into account.
[0093] The porosity of the porous-film of the present embodiment is preferably more than 70% and less than 95%, more preferably more than 85% and less than 95%, further preferably more than 90% and less than 95%. By making the porosity more than 70%, the IgG recovery rate can be improved. On the other hand, if the porosity is too high, the strength of the porous-film is sometimes insufficient. By setting the porosity to the above range, it is possible to take into account both filterability and the strength relative to the filtration pressure. As described later, the porosity of the porous-film can be calculated according to the quality of the water when the void portion of the porous-film is made to contain water and the quality of the porous-film after drying.
[0094] (use)
[0095] The porous membrane of this embodiment can be used, for example, for purification based on cation exchange (purification method). The porous membrane of this embodiment is suitable for use in the process of removing inclusions from cell culture fluid and purifying antibodies (IgG, etc.) in order to adsorb and remove positively charged substances contained in proteins (HCP) from host cells, etc., when manufacturing antibody drugs, for example. In such applications, the clogging suppression effect of the porous membrane of this embodiment is particularly useful.
[0096] <Method for producing porous film>
[0097] Hereinafter, regarding the method for producing the porous membrane, one embodiment of a hollow fiber membrane will be described.
[0098] The hollow fiber membrane of the present embodiment can be produced, for example, by the following production method.
[0099] The manufacturing method of the hollow fiber membrane of this embodiment includes the following spinning process: the spinning stock solution and the inner liquid are discharged from the double-layer tubular nozzle into the coagulation liquid through the aerial traveling part, the above-mentioned spinning stock solution is coagulated in the above-mentioned coagulation liquid, and the coagulated product of the above-mentioned spinning stock solution is pulled out from the above-mentioned coagulation liquid, thereby obtaining the hollow fiber membrane.
[0100] The spinning solution comprises: a resin raw material containing polyethersulfone, a solvent and a non-solvent.
[0101] The above-mentioned internal liquid contains water.
[0102] In the above method for producing a hollow fiber membrane,
[0103] The total concentration of components other than water in the internal liquid (internal liquid concentration) is preferably 70 to 90% by mass.
[0104] The temperature of the coagulation liquid is preferably 40 to 60°C.
[0105] In addition, the air gap length (AG length) described later is preferably 10 to 80 mm.
[0106] 〔Spinning process〕
[0107] Reference Figure 1 In the spinning process, a spinning dope 10a and an inner liquid 10b are discharged from a double-layer tubular nozzle 11 through an air travel portion (air gap) 20 into a coagulation liquid 21, the spinning dope is coagulated in the coagulation liquid 21, and the coagulated product of the spinning dope is pulled out from the coagulation liquid 21, thereby obtaining a hollow fiber membrane 3. The pulling out of the hollow fiber membrane is performed, for example, by liquid guides 12, 13 and rollers 14, 15, 16. It should be noted that the hollow fiber membrane 3 pulled out from the coagulation liquid 21 is, for example, immersed in a water bath 22 and then wound up by a winder 23.
[0108] The nozzle 11 is a double-layered tube, comprising an outer tube and an inner tube disposed inside the outer tube. The spinning solution is discharged from the gap (slit) between the outer tube and the inner tube, and the inner solution is discharged from the inner tube. The inner diameter of the outer tube is preferably 500 to 1500 μm, more preferably 600 to 1200 μm. The outer diameter of the inner tube is preferably 150 to 700 μm, more preferably 150 to 600 μm. It should be noted that the outer diameter of the inner tube is preferably the same as the inner diameter of the hollow fiber membrane.
[0109] The straight distance of the air traveling portion 20 (the distance between the tip of the nozzle 11 and the liquid surface of the coagulation liquid 21 ), that is, the air gap length (AG length) is preferably 10 to 100 mm, and more preferably 10 to 80 mm.
[0110] It should be noted that the hollow fiber membrane obtained by the spinning process can be further subjected to a cleaning process (water washing process) using pure water. The flow of water in the water washing process is preferably a flow in the opposite direction to the moving direction of the hollow fiber membrane (convection), but can also be a flow in the same direction as the moving direction of the hollow fiber membrane (cocurrent).
[0111] (Spinning solution)
[0112] The spinning solution 10a includes, for example, a resin raw material including the above-mentioned polyethersulfone, sulfonated polyarylether copolymer, and polyvinylpyrrolidone, a solvent, and a non-solvent.
[0113] The temperature of the spinning solution in the nozzle 11 (discharge temperature) is preferably 40 to 80°C, more preferably 50 to 70°C.
[0114] The concentration of polyethersulfone in the spinning solution is preferably 10 to 30% by mass, more preferably 10 to 25% by mass. If the concentration of polyethersulfone is too low, the strength of the hollow fiber membrane may be reduced. On the other hand, if the concentration of polyethersulfone is too high, the viscosity of the spinning solution may be too high, making it difficult to perform spinning.
[0115] The concentration of the vinyl pyrrolidone polymer in the spinning solution is preferably 0.5 to 20% by mass, more preferably 1 to 15% by mass. If the concentration of the vinyl pyrrolidone polymer is too low, when used for cation exchange, proteins in the cell culture solution are easily blocked by accumulation, and the performance degradation over time sometimes becomes faster. On the other hand, if the concentration of the vinyl pyrrolidone polymer is too high, the viscosity of the spinning solution becomes too high, and it is sometimes difficult to implement spinning.
[0116] The concentration of the negatively charged polymer in the spinning solution is preferably 1 to 5% by mass, more preferably 2 to 5% by mass. If the concentration of the negatively charged polymer is too low, the adsorption and removal of positively charged substances in HCP in the cell culture solution becomes insufficient when used for cation exchange, and sometimes unnecessary components leak out. On the other hand, if the concentration of the negatively charged polymer is too high, the viscosity of the spinning solution becomes too high, and sometimes it is difficult to implement spinning.
[0117] The solvent is a liquid that can dissolve polyethersulfone. The solvent is preferably a polar solvent, preferably soluble in water. The polar solvent is preferably an aprotic polar solvent. Examples of the aprotic polar solvent include N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), acetonitrile, and the like.
[0118] The non-solvent is a liquid (excluding water) that does not dissolve polyethersulfone. Examples of the non-solvent include glycol esters, glycerol, and alcohols, and glycol esters are preferred. Examples of glycol esters include ethylene glycol, triethylene glycol (TEG), polyethylene glycol (polyethylene glycol 200, polyethylene glycol 400, etc.), and propylene glycol.
[0119] In the spinning solution, the mass ratio of the solvent (S) to the non-solvent (NS) (S / NS ratio) is preferably 35 / 65 to 55 / 45, and more preferably 40 / 60 to 50 / 50. If the S / NS ratio in the spinning solution becomes too small, the dissolution of polyethersulfone becomes unstable, so that the spinning stability is sometimes reduced, or an asymmetric structure suitable for the use of the present invention cannot be obtained. If the S / NS ratio becomes large, a hollow fiber membrane with an asymmetric structure may not be obtained, or the spinning stability is reduced.
[0120] It should be noted that the spinning solution may further contain water in addition to the solvent and the non-solvent.
[0121] The order of adding the resin raw material, the solvent, and the non-solvent to be the constituent material of the hollow fiber membrane and the mixing method of the materials when mixing are not particularly limited.
[0122] (internal fluid)
[0123] The inner liquid contains water. The content of water in the inner liquid is preferably 5 to 30% by mass, more preferably 10 to 25% by mass.
[0124] The internal solution may contain a solvent, a non-solvent, etc. in addition to water. Examples of the non-solvent include ethylene glycol, triethylene glycol (TEG), polyethylene glycol 200 or 400, glycerol, propylene glycol, etc. Examples of the solvent include N-methylpyrrolidone (NMP), dimethylacetamide, dimethylformamide, dimethyl sulfoxide, etc.
[0125] If the water content of the inner liquid is low and the content of each solvent is high, the solidification speed of the inner side of the hollow fiber membrane becomes slow, the phase separation time is prolonged, and a sparse structure is constructed inside the hollow fiber membrane. On the other hand, if the water content is high and the solvent content is low, the solidification speed of the inner side of the hollow fiber membrane becomes fast, the phase separation time is shortened, and a dense structure is constructed inside the hollow fiber membrane.
[0126] In order to obtain the hollow fiber membrane of the present embodiment showing a sparse structure inside the membrane, it is preferred to increase the concentration of components (solvent, non-solvent, etc.) other than water contained in the inner liquid (inner liquid concentration). The inner liquid concentration is preferably 70 to 95% by mass, more preferably 75 to 90% by mass. The ratio of the mass of the solvent to the non-solvent in the inner liquid (solvent / non-solvent) is, for example, 40 / 60 to 50 / 50.
[0127] When the spinning solution 10a and the internal solution 10b are discharged from the double-tube-shaped nozzle 11, a temperature difference may be provided between the spinning solution and the internal solution.
[0128] (Coagulation liquid)
[0129] The coagulation liquid preferably contains a solvent and a non-solvent. It should be noted that the solvent and the non-solvent can be one kind respectively, or a mixture of multiple kinds. If the content of each solvent is too high, the coagulation rate of the outside of the hollow fiber membrane slows down, the phase separation time is prolonged, and a sparse structure is constructed on the outside of the hollow fiber membrane. In addition, if the water content is high and the solvent content is too low, the coagulation rate of the outside of the hollow fiber membrane is accelerated, the phase separation time is shortened, and a dense structure is constructed on the outside of the hollow fiber membrane. In order to obtain a hollow fiber membrane of this embodiment with a dense outer side of the membrane, the ratio of the total amount of solvent to non-solvent in the coagulation liquid (concentration of coagulation liquid: CB concentration) is preferably 20 to 60% by mass, and more preferably 30 to 45% by mass. The ratio of the mass of the solvent in the coagulation liquid to the non-solvent (solvent / non-solvent) is, for example, 40 / 60 to 50 / 50.
[0130] In addition, the temperature of the coagulation liquid also has a great influence on the coagulation time of the membrane. If the temperature of the coagulation liquid is high, the coagulation speed of the outer side of the hollow fiber membrane slows down, the phase separation time is prolonged, and a sparse structure is constructed on the outer side of the hollow fiber membrane. In addition, if the temperature of the coagulation liquid is low, the coagulation speed of the outer side of the hollow fiber membrane speeds up, the phase separation time is shortened, and a dense structure is constructed on the outer side of the hollow fiber membrane. In order to obtain the hollow fiber membrane of the present embodiment with a dense outer side of the membrane, the temperature of the coagulation liquid is preferably 30 to 70°C, more preferably 40 to 60°C.
[0131] If the coagulation rate of the outer side of the hollow fiber membrane based on the concentration and temperature of the coagulation liquid is fast relative to the coagulation rate of the inner side of the hollow fiber membrane based on the concentration of the inner liquid, the inner surface side becomes a sparse structure, and the outer surface side becomes dense. If the coagulation rate of the outer side of the membrane is too fast relative to the inner side, the outer side of the membrane becomes too dense, and useful components such as IgG cannot pass through. On the contrary, if it is slow, the pore size of the outer side of the membrane is large, and the inclusions that are to be prevented from passing through. If it is further too slow, the inner surface side becomes dense, and the outer surface side becomes sparse, and the liquid cannot penetrate from the inner surface side of the membrane into the interior of the membrane. Therefore, in order to obtain the hollow fiber membrane of the present embodiment with a sparse structure on the inner surface side, a dense outer surface side, and an asymmetric structure such as allowing useful components to pass through and preventing inclusions, it is important to balance the above-mentioned inner liquid concentration with the concentration and temperature of the coagulation liquid.
[0132] Example
[0133] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0134] (Preparation of Sulfonated Polyarylene Ether Copolymer)
[0135] 3,3'-disulfo-4,4'-dichlorodiphenylsulfone disodium salt (hereinafter referred to as S-DCDPS), 2,6-dichlorobenzonitrile (hereinafter referred to as DCBN), 4,4'-biphenol (hereinafter referred to as BP), potassium carbonate, and NMP were weighed into a four-necked flask so that S-DCDPS became 11.6 mass%, DCBN became 5.0 mass%, BP became 9.6 mass%, potassium carbonate became 8.2 mass%, and NMP became 65.6 mass%. Molecular sieves were added and nitrogen was flowed. After stirring at 150°C for 50 minutes, the reaction temperature was raised to 195°C to 200°C, and the reaction was continued with the goal of sufficiently improving the viscosity of the system. Then, the reaction was allowed to cool, and after cooling, the precipitated molecular sieves were removed to precipitate the polymer in water. After washing the obtained polymer in boiling water for 1 hour, it was carefully washed with pure water to completely remove the residual potassium carbonate. Then, the polymer after the potassium carbonate was removed was dried to obtain a sulfonated polyarylether copolymer. The obtained SPN was a copolymer of the above formula (1) and formula (2), the constituent molar ratio of (1) was 0.56, and the constituent molar ratio of (2) was 0.44.
[0136] [Example 1]
[0137] The hollow fiber membrane of Example 1 was produced by basically the same method as the method for producing the hollow fiber membrane described in the embodiment.
[0138] It should be noted that in the spinning process, the obtained spinning dope is discharged together with the inner liquid from the heated tubular nozzle, passed through the dry section (air traveling section 20: air gap) isolated from the external gas by the spinning tube, solidified in the coagulation bath, passed through the water washing bath, and then wound up by a wringing machine (Japanese: かせ取り機) (winding machine 23) at a specified spinning speed. The specific conditions are as follows.
[0139] <Preparation of Spinning Dope>
[0140] Mix 16.0% by mass of polyethersulfone (PES, SUMIKAEXCEL 4800 manufactured by Sumitomo Chemical), 4.0% by mass of the above-mentioned sulfonated polyarylether copolymer (SPN, manufactured by Toyobo), 2.0% by mass of polyvinylpyrrolidone K-90 (PVP, manufactured by Nippon Shokubai), 46.8% by mass of N-methyl-2-pyrrolidone (NMP, manufactured by Mitsubishi Chemical Corporation), and 31.2% by mass of triethylene glycol (TEG, manufactured by Mitsubishi Chemical Corporation), and heat and dissolve uniformly to prepare a spinning dope.
[0141] <Composition of Inner Liquid>
[0142] Mix a mixed solution with a mass ratio of NMP (solvent) to TEG (non-solvent) (S / NS ratio) of NMP / TEG = 60 / 40 with reverse osmosis (RO) water as the inner liquid. It should be noted that the total concentration of the solvent and non-solvent in the inner liquid (inner liquid concentration) is 80% by mass, and RO water is 20% by mass.
[0143] <Composition of Coagulating Liquid>
[0144] Mix a mixed solution with a mass ratio of NMP (solvent) to TEG (non-solvent) (S / NS ratio) of NMP / TEG = 60 / 40 with reverse osmosis (RO) water to prepare a coagulating liquid. It should be noted that the total concentration of the solvent and non-solvent in the coagulating liquid (CB concentration) is 40% by mass, and RO water is 60% by mass.
[0145] <Conditions of Spinning Process>
[0146] Discharge temperature (set temperature) of spinning dope: 60 °C
[0147] Distance of air traveling section (air gap length: AG length): 40 mm
[0148] Pulling speed (spinning speed): 20 m / min
[0149] <Conditions of Water Washing Process>
[0150] Flow of water washing tank (water washing bath): Convection
[0151] Temperature: 45℃
[0152] The bundle of hollow fiber membranes obtained by the above process was cut into a certain length, wrapped with gauze, washed with RO water at 80°C, and immersed in a glycerol aqueous solution with a glycerol concentration of 80% by mass. It should be noted that glycerol produced by NOF was used to prepare the glycerol aqueous solution. Then, it was taken out from the glycerol aqueous solution and dried at 60°C with a hot air dryer. Thus, a dried hollow fiber membrane was obtained.
[0153] The obtained hollow fiber membrane had a dense layer on the outer surface side, an inner diameter of 265 μm, an outer diameter of 365 μm, and a thickness (membrane thickness) of 50 μm.
[0154] [Example 2]
[0155] In Example 2, the composition ratio of the spinning solution (PES, PVP (K-90), SPN, NMP, and TEG) was changed as shown in Table 1. A hollow fiber membrane of Example 2 was produced in the same manner as in Example 1 except for this. It should be noted that "%" in Table 1 means "mass %".
[0156] [Example 3]
[0157] In Example 3, the temperature of the coagulation liquid was changed as shown in Table 1. The other conditions were the same as in Example 1, and the hollow fiber membrane of Example 3 was produced.
[0158] [Comparative Example 1]
[0159] In Comparative Example 1, the internal solution concentration, the temperature of the coagulation solution, the AG length, and the spinning speed were changed as shown in Table 1. Except for the above, the hollow fiber membrane of Comparative Example 1 was produced in the same manner as in Example 1.
[0160] [Comparative Example 2]
[0161] In Comparative Example 2, the composition of the spinning solution was changed as shown in Table 1. Except for this, the same procedure as in Comparative Example 1 was carried out to obtain a hollow fiber membrane of Comparative Example 2.
[0162] [Comparative Example 3]
[0163] In Comparative Example 3, the composition of the spinning solution, the internal solution concentration, the S / NS ratio of the internal solution, the AG length, the temperature of the coagulation solution, the CB concentration, and the S / NS ratio of the coagulation solution were changed as shown in Table 1. A hollow fiber membrane of Comparative Example 3 was obtained in the same manner as in Comparative Example 1 except for the above.
[0164] [Comparative Example 4]
[0165] In Comparative Example 4, the same operation as in Example 1 was carried out to obtain a hollow fiber membrane.
[0166] [Table 1]
[0167]
[0168] The following items were measured for each of the above-mentioned Examples and Comparative Examples. The measurement results are shown in Table 2. It should be noted that the parts without numerical values in Table 2 were not measured.
[0169] [Inner diameter, outer diameter and membrane thickness of hollow fiber membrane]
[0170] The inner diameter, outer diameter, and membrane thickness of the hollow fiber membranes of the above-mentioned Examples and Comparative Examples were measured by the following methods.
[0171] To the extent that the hollow fiber membrane does not fall off, an appropriate number of hollow fiber membranes are passed through a hole with a diameter of 3 mm opened in the center of a glass slide, and the hollow fiber membrane is cut with a razor along the upper and lower surfaces of the glass slide to obtain a hollow fiber membrane cross-sectional sample. For the obtained hollow fiber membrane cross-sectional sample, the inner diameter and outer diameter of the hollow fiber membrane are measured using a projector (Nikon PROFILE PROJECTOR V-12).
[0172] Specifically, the dimensions of the outer surface of the hollow fiber membrane in the XX direction and the YY direction (two orthogonal directions on the cross section) are measured for each hollow fiber membrane cross section, and the arithmetic mean of these values is used as the outer diameter of the cross section of the hollow fiber membrane. In addition, the dimensions of the hollow part in the XX direction and the YY direction (two orthogonal directions on the cross section) are measured for each hollow fiber membrane cross section, and the arithmetic mean is used as the inner diameter of the cross section of the hollow fiber membrane. It should be noted that 10 cross sections are measured in the same manner, and the average values are used as the inner diameter and outer diameter.
[0173] The membrane thickness (average value) was calculated by the formula of “(outer diameter−inner diameter) / 2” based on the inner diameter of the hollow fiber membrane and the measurement result (average value) of the inner diameter.
[0174] [Porosity]
[0175] The porosity of the porous film was measured by the following procedure.
[0176] (1) The porous membrane bundle fully immersed in pure water was centrifuged at 900 rpm for 5 minutes to remove the liquid.
[0177] (2) The mass (W) of the porous membrane after the liquid removal is measured.
[0178] (3) The mass (P) of the porous membrane after absolute drying in a dryer is measured.
[0179] (4) The void ratio (φ) is calculated by the following formula.
[0180] φ (%) = W / (W + P / density of polymer) × 100
[0181] Here, the density of the polymer is calculated using the density of the polymer with the highest content in the membrane. For example, the density of polyethersulfone is 1.37 g / cm 3 .
[0182] [SEM image]
[0183] A SEM image of a cross section of the hollow fiber membrane was obtained by the following procedure.
[0184] (1) The hollow fiber membrane was gently washed with water, and the sample was frozen with liquid nitrogen and cut.
[0185] (2) The obtained sample is fixed on a sample stand so that the cut surface can be observed, and carbon is deposited by sputtering.
[0186] (3) The sample after carbon deposition was observed using a scanning electron microscope (S-2500 manufactured by Hitachi) at an accelerating voltage of 10 kV to obtain a SEM image.
[0187] It should be noted that the SEM images of Example 1 and Comparative Example 1 are shown in Figure 8 and Fig. 9 .according to Figure 8 It was confirmed that the hollow fiber membrane of Example 1 had an asymmetric structure, and had a structure in which the inner surface side was sparse and the outer surface side was dense.
[0188] [Colloidal gold transmittance]
[0189] The transmittance of 10 nm colloidal gold (colloidal gold having an average particle size of 10 nm) and 30 nm colloidal gold (colloidal gold having an average particle size of 30 nm) was measured as follows using a hollow fiber membrane as an example.
[0190] <Manufacturing of Ring Micromodule>
[0191] A bundle of multiple hollow fiber membranes cut into a length of about 40 cm was bent so that the ends overlapped, and the ends were inserted into a tube (sheath) and fixed with hot-melt resin. A portion of the adhesive fixing portion was cut off to produce a ring-shaped micromodule with the hollow portion of the hollow fiber membrane opened (see Fig.11 ). The number of hollow fiber membranes is appropriately set.
[0192] <Preparation of colloidal gold dispersion>
[0193] After mixing 6 mL of 10 nm and 30 nm colloidal gold homogenate (colloidal gold standard product manufactured by BBI Solutions) and 3 mL of 2.0 mass % bovine serum albumin (Albumin, Bovine Serum, FV, pH 5.2 manufactured by Nacalai Tesque) aqueous solution, 3 mL of 0.4 mass % glutathione (reduced form) aqueous solution (manufactured by Nacalai Tesque) was added.
[0194] <Colloidal gold penetration experiment>
[0195] Using the annular micromodule produced above,
[0196] (1) The colloidal gold dispersion was dead-end filtered at a pressure of 1000 hPa and the filtrate was sampled (refer to Fig.12 ).
[0197] (2) Calculate the transmittance of colloidal gold from the following absorbance (wavelength 540 nm) measurement value.
[0198] Transmittance = ratio of absorbance of colloidal gold dispersion to absorbance of filtrate
[0199] [Thickness of the Colloidal Gold Capture Layer of 20nm]
[0200] When the measurement liquid (20 nm colloidal gold dispersion) was filtered from the inside to the outside of the hollow fiber membrane by the following procedure, the thickness of the layer capturing the 20 nm colloidal gold (capturing layer) was measured.
[0201] <Preparation of colloidal gold dispersion>
[0202] After 6 mL of a 20 nm colloidal gold homogenate (Gold Colloid manufactured by BBI Solutions) and 3 mL of a 2.0 mass % bovine serum albumin (Albumin, Bovine Serum, FV, pH 5.2 manufactured by Nacalai Tesque) aqueous solution were mixed, 3 mL of a 0.4 mass % glutathione (reduced form) aqueous solution (manufactured by Nacalai Tesque) was added.
[0203] <Colloidal gold capture experiment>
[0204] (1) The measurement liquid (20 nm colloidal gold dispersion) was dead-end filtered in the same manner as the above-mentioned measurement of colloidal gold transmittance (refer to Figure 7 ), the cross-section of the hollow fiber membrane (sample) after filtration was imaged using a microscope. (The images of Comparative Example 1 and Example 1 are shown in Fig.10 (a) and (b).
[0205] (2) The captured image was binarized (WinROOF 2013) and the distance from the primary side (the inner surface of the hollow fiber membrane) to the colloidal gold capture position was measured. Fig.10 In (b), the distance from the inner surface of the hollow fiber membrane to the position indicated by the arrow of the colloidal gold capturing layer is measured.
[0206] In addition, in Table 2, the ratio of the thickness of the capture layer to the thickness of the hollow fiber membrane is also shown.
[0207] It should be noted that in Comparative Example 4, 20 nm of colloidal gold was filtered from the outside to the inside of the hollow fiber membrane of Example 1, and the thickness of the capture layer was measured in the same manner as above. Fig.10 (c) shows a SEM image of the cross section of the hollow fiber membrane after filtration. The measurement results confirmed that the thickness of the capture layer was 0, and when filtering from the outside to the inside of the hollow fiber membrane, the 20 nm colloidal gold did not penetrate into the inside of the hollow fiber membrane in the thickness direction.
[0208] [Cation exchange capacity]
[0209] Taking a hollow fiber membrane as an example, the cation exchange capacity per unit volume of the porous membrane is measured as follows: It should be noted that the cation exchange capacity per unit volume of the porous membrane is an index showing the performance of removing negatively charged substances.
[0210] Specifically, the measurement is performed by the following steps (1) to (8).
[0211] (1) Based on the measured value, the density of the hollow fiber membrane (sample) was calculated according to the following formula.
[0212] Density = dry weight / (membrane cross-sectional area × length × number of roots)
[0213] (2) Immerse 10 pieces of sample (1 cm x 10) in 1M HCl for 30 min.
[0214] (3) Transfer the sample to a suction flask and filter it.
[0215] (4) Flow water directly through the sample until the liquid after suction appears neutral, then filter it.
[0216] (5) Take out the sample and immerse it in 1 M NaCl solution.
[0217] (6) Add phenolphthalein solution to the 1 M NaCl solution in which the sample is immersed, and titrate with 0.01 M NaOH.
[0218] (7) The end point is the point where the phenolphthalein solution becomes colored.
[0219] (8) Calculate the cation exchange capacity according to the following formula.
[0220] Cation exchange capacity = titration amount (mL) / [sample amount (0.1g) / density (g / mL)]
[0221] [IgG recovery rate and IgG aggregation inhibition rate]
[0222] The IgG recovery rate and IgG aggregate inhibition rate using the hollow fiber membrane were measured by the following procedure.
[0223] <Module production>
[0224] Insert the hollow fiber membrane bundle into the cylindrical container and fix the two ends with an adhesive. Cut the ends to obtain a module with two open ends. The number of hollow fiber membranes is appropriately set. It should be noted that an inlet and outlet (Japanese: ポート) are set at two locations on the cylindrical surface of the cylindrical cylindrical container so that the fluid can perfuse both the outer surface and the inner surface of the hollow fiber membrane.
[0225] <Calculation of membrane area>
[0226] The membrane area A of the module is determined by the following formula based on the inner diameter of the hollow fiber membrane.
[0227] A=n×π×ID×L
[0228] Here, n is the number of hollow fiber membranes in the module, π is the circumference of a circle, ID is the inner diameter of the hollow fiber membrane [m], and L is the effective length of the hollow fiber membrane in the module [m].
[0229] <Calculation of membrane volume>
[0230] The membrane volume V [mL] of the module was determined by the following formula based on the inner diameter and outer diameter of the hollow fiber membrane.
[0231] V=n×π×{(OD / 2) 2 -(ID / 2) 2}×L
[0232] Here, n is the number of hollow fiber membranes in the module, π is the circumference of a circle, ID is the inner diameter [cm] of the hollow fiber membrane, OD is the outer diameter [cm] of the hollow fiber membrane, and L is the effective length [cm] of the hollow fiber membrane in the module.
[0233] <Adjustment of each measurement solution>
[0234] (1) Prepare the following measurement solutions.
[0235] (i) IgG recovery rate
[0236] A phosphate buffer was added so that the concentration of IVIG manufactured by Seracare was 0.05%, thereby preparing a measurement solution.
[0237] (ii) IgG aggregation inhibition rate
[0238] HCl was added to the measurement solution of (i) above to adjust the pH to 1.0 or less, and then 5 hours later, the pH was neutralized using NaOH to prepare the measurement solution of (ii).
[0239] <IgG recovery and IgG aggregation inhibition test>
[0240] (2) Use the above module to perform dead-end filtration on the measurement liquid (refer to Figure 7 ), and sample the filtrate.
[0241] (3) The absorbance (wavelength: 280 nm) of each of the measurement liquid and the filtrate was measured.
[0242] (4) Using a multi-specimen nanoparticle size measurement system (product name: nano SAQLA, manufacturer: Otsuka Electronics Co., Ltd., analysis method: Marquardt method, standard: number distribution), the particle size distribution of the measurement liquid and the filtrate was measured to determine the relative frequency of particles with a diameter of less than 50 nm and particles with a diameter of 50 nm or more.
[0243] (5) Calculate the IgG recovery rate [%] and IgG aggregation inhibition rate [%] according to the following formula.
[0244] IgG recovery rate [%] = (absorbance of filtrate × relative frequency of particles in filtrate with a diameter less than 50 nm) / (absorbance of assay solution × relative frequency of particles in assay solution with a diameter less than 50 nm) × 100
[0245] IgG aggregation inhibition rate [%] = 100 - ((absorbance of filtrate × relative frequency of particles of filtrate with a diameter of 50 nm or more) / (absorbance of assay solution × relative frequency of particles of assay solution with a diameter of 50 nm or more)) × 100
[0246] [Lysozyme adsorption amount]
[0247] The amount of lysozyme adsorbed per unit volume of the hollow fiber membrane was measured by the following procedure. The amount of lysozyme adsorbed was defined as the amount of lysozyme adsorbed on the hollow fiber membrane until 10% of the lysozyme was broken through.
[0248] (1) Dulbecco's phosphate buffered saline powder commercially available from Fujifilm Wako Pure Chemical Industries, Ltd. was dissolved in distilled water to a total volume of 500 mL to obtain a phosphate buffer solution having a concentration of 1% by mass. Lysozyme commercially available from Fujifilm Wako Pure Chemical Industries, Ltd. and an egg white source were added to the buffer solution to a concentration of 0.22 mg / mL to prepare a measurement solution.
[0249] (2) For the above module with 6 hollow fiber membrane fibers, the flow rate per unit membrane area was set to 700 mL / m 2 , the measurement liquid is transported to the hollow part and dead-end filtration is performed. The filtrate is collected every 10 minutes from the start of filtration, and the filtrate volume Z of each filtrate segment (Japanese: フラクション) is measured. n .
[0250] Here, n represents a filtrate stage number, and is an ordinal number with the first filtrate stage number being set to 1.
[0251] (3) The absorbance at 280 nm of the measurement liquid and each filtrate fraction is measured, and the lysozyme concentration in each filtrate fraction and the measurement liquid, as well as the ratio Y of the lysozyme concentration in each filtrate fraction to the lysozyme concentration in the measurement liquid are calculated based on the calibration curve prepared in advance. n .
[0252] Y n =280nm absorbance of the filtrate / 280nm absorbance of the assay solution
[0253] (4) The cumulative filtration volume W from the start of filtration to the end of recovery of each filtrate stage n The ratio of the above lysozyme concentration Y n The relationship is as Fig.13 The histogram is shown.
[0254] W n =Z1+Z2+···+Z n
[0255] (5) Fig.13 In the bar graph, draw a straight line connecting the centers of the upper ends of adjacent filtrate segments, draw this line as a straight line of lysozyme concentration ratio = 0.1, and take the point where the two straight lines intersect as the 10% breakthrough point, and calculate the cumulative filtration amount X until that moment.
[0256] (6) When the W closest to X is n Set to W m When the total amount of lysozyme contained in the filtrate segments from (m-1)th to (m-1)th is defined as A, half of the amount of lysozyme contained in the mth filtrate segment is defined as B, and the cumulative filtration amount is defined as (W m +W m-1) / 2 to X, the approximate value of the amount of lysozyme contained in the filtrate was set as C, and was calculated by the following formula.
[0257] A=(Z1×Y1+Z2×Y2+···+Z m-1 ×Y m-1 ) × lysozyme concentration in the assay solution
[0258] B=Z m ×Y m / 2×lysozyme concentration in the assay solution
[0259] C = (X-(W m +W m-1 ) / 2)×(Y m +0.1) / 2×lysozyme concentration in the assay solution
[0260] (7) The total of A, B, and C is taken as the cumulative leakage amount of lysozyme up to the cumulative filtration amount X.
[0261] Cumulative leakage = A + B + C
[0262] (8) The amount of lysozyme supplied until the cumulative filtration amount X (cumulative supply amount) is calculated by the following formula.
[0263] Cumulative supply amount = X × lysozyme concentration in the assay solution
[0264] (9) The amount of lysozyme adsorbed on the hollow fiber membrane until the cumulative filtration amount X (cumulative adsorption amount) was calculated by the following formula.
[0265] Cumulative adsorption amount = total supply amount - cumulative leakage amount
[0266] (10) The amount of lysozyme adsorbed per unit volume of the hollow fiber membrane (lysozyme adsorption per unit volume) was determined by the following formula.
[0267] Lysozyme adsorption per unit volume = the above cumulative adsorption / membrane volume
[0268] It should be noted that lysozyme was used for evaluation as a representative substance of positively charged substances, and a large amount of lysozyme adsorption indicates a high adsorption capacity of positively charged substances.
[0269] Figure 5 This is a graph showing the amount of lysozyme adsorbed per unit volume of the hollow fiber membranes of Comparative Example 1 and Example 1. Figure 5 , the measurement results of the amount of lysozyme adsorbed on a PES membrane (hollow fiber membrane made of polyethersulfone) and a Mustang S (flat membrane made by Pall Corporation) are shown together.
[0270] [Cumulative filtration volume]
[0271] The cumulative filtration amount per unit area of the hollow fiber membrane was measured by the following procedure.
[0272] (1) 9.6 g of Dulbecco PBS (-) powder "Nissui" commercially available from Nissui Pharmaceutical Co., Ltd. was dissolved in distilled water to a total of 1000 mL to obtain PBS. Seracare IVIG was diluted with the buffer solution and the pH was adjusted to 7.3 with a 1 mol / L sodium hydroxide aqueous solution. The concentration of IVIG after dilution and pH adjustment was adjusted to 0.05% by mass.
[0273] (2) The measurement liquid was placed in a pressure tank and kept warm at 25°C. For the module having 6 hollow fiber membrane fibers, dead-end filtration was performed while controlling the pressure with a regulator so that the filtration pressure became 1.0 bar. The filtrate was sampled at intervals of 30 seconds.
[0274] (3) Calculate the cumulative filtration volume per unit area of the hollow fiber membrane relative to the filtration time TPn [L / m 2 ] and record.
[0275] TPn=Wn / 1.0 / A / 1000
[0276] Here, W is the total amount of filtrate recovered n minutes after the start of filtration [mL], 1.0 is the density of the test solution [g / cc], and A is the membrane area of the module [m 2 ].
[0277] Table 2 shows the cumulative filtration amount after 15 minutes from the start of filtration. Figure 6 This is a graph showing the relationship between the filtration time and the cumulative filtration capacity per unit area for the hollow fiber membranes of Comparative Example 1 and Example 1.
[0278] [Table 2]
[0279]
[0280] From the results shown in Example 1 and Comparative Example 3 in Table 2, it can be seen that when the transmittance of 10 nm colloidal gold is 9% or more, the recovery rate of IgG has a high value of 90% or more.
[0281] On the other hand, it is found that Comparative Example 3 does not contain a negatively charged polymer and does not have the ability to adsorb a positively charged substance (representative substance: lysozyme).
[0282] In addition, according to Figure 6 (a) It is believed that in Comparative Example 1 having a dense layer on the first surface (inner surface), the rate of increase in the cumulative filtration amount decreased over time, and clogging occurred. Figure 6As shown in (b), in Example 1 having a dense layer on the second surface (outer surface) side, the rate of increase of the cumulative filtration amount is substantially constant, and it is considered that no clogging occurs. According to these results and the cumulative filtration amount shown in Table 2, in the porous membrane of the present invention, by having a dense layer on the second surface (outer surface) side, the reduction in filtration performance caused by clogging is suppressed.
[0283] In addition, Example 1 and Comparative Example 4 in Table 2 are comparisons when the first surface side and the second surface side are used as opposite directions in the same porous membrane, but in Comparative Example 4 having a structure with a dense layer on the first surface side, a 20nm capture layer of colloidal gold was not confirmed inside the membrane, and it can be seen that colloidal gold is deposited near the first surface side. It can be seen from this that the reduction in filtration performance caused by clogging is suppressed by having a structure with a dense layer on the second surface (outer surface) side.
[0284] Furthermore, the results shown in Examples 1 to 3 show that if the membrane is impermeable to 30 nm colloidal gold, the permeation of IgG aggregates can be prevented.
[0285] Based on the above results, it can be seen that by containing a negatively charged polymer, it has the ability to adsorb and remove positively charged substances, by having the permeability of 10nm colloidal gold, it has a high IgG recovery rate, by having a 20nm colloidal gold capture layer inside the membrane, it can inhibit clogging, and by not having the permeability of 30nm colloidal gold, it can prevent the permeation of IgG aggregates.
[0286] Description of Reference Numerals
[0287] 10a: spinning solution, 10b: internal solution, 11: nozzle, 12, 13: liquid guides, 14, 15, 16: rollers, 20: aerial travel section, 21: coagulation solution, 22: water washing bath, 23: winder, 3: hollow fiber membrane, 4: large-sized component, 5: small-sized component.
Claims
1. A porous membrane comprising a polymer having a negative charge, The porous membrane has a non-uniform structure in the thickness direction, wherein the first surface is sparse and the second surface is dense. In the porous membrane, the transmittance of colloidal gold having an average particle size of 10 nm from the first surface side to the second surface side is 5% or more, The porous membrane does not have the ability to transmit colloidal gold having an average particle size of 30 nm from the first surface side to the second surface side, When colloidal gold having an average particle size of 20 nm is allowed to pass from the first surface side to the second surface side of the porous membrane, the ratio of the thickness of the capture layer to the thickness of the porous membrane is greater than 10%, and the capture layer is a layer that captures the colloidal gold having an average particle size of 20 nm.
2. The porous membrane according to claim 1, wherein The porous membrane further comprises a hydrophobic polymer and a hydrophilic polymer.
3. The porous membrane according to claim 2, wherein The hydrophobic polymer is at least one of polysulfone and polyethersulfone.
4. The porous membrane according to claim 2, wherein The hydrophilic polymer is at least one of polyvinyl pyrrolidone and a copolymer of vinyl pyrrolidone and vinyl acetate.
5. The porous membrane according to claim 1 or 2, wherein The negatively charged polymer comprises, as copolymer components, repeating units of a hydrophobic segment represented by the following formula (1) and repeating units of a hydrophilic segment represented by the following formula (2), The molar ratio of the formula (1) is 0.50 to 0.65, the molar ratio of the formula (2) is 0.35 to 0.50, the total of the molar ratio of the formula (1) and the molar ratio of the formula (2) is 1.00, R1 and R2 represent "-SO3M", and M represents a metal element. The porous membrane according to claim 1 or 2, which has a hollow fiber membrane shape in which the inner surface side is sparse and the outer surface side is dense.
7. The porous membrane according to claim 1 or 2, which is used for purification by cation exchange. A purification method using the porous membrane according to claim 1.